Efficacy and safety study of ultrasound guided microwave ablation of large benign thyroid nodules - WU Dan*，FAN Boqiang，XU Ting，HU Cuining，TANG Wei (Zhongguo linchuang yanjiu)
Objective To retrospectively evaluate the efficacy and safety of microwave ablation （MWA）in the treatment of large benign thyroid nodules. Methods Patients with large thyroid nodules who underwent ultrasound- guided MWA at Jiangsu Province Hospital and Jiangsu Province Official Hospital from March 2013 to October 2018 were included. A total of 191 patients with 397 nodules were enrolled. All nodules were confirmed as benign by ultrasound-guided fine-needle aspiration cytology（FNA）， with the main nodule volume＞20 mL. Intraoperative and postoperative complications were recorded. Nodule volume was assessed at 1，3，6，12，and 24 months post-treatment. Volume changes and volume reduction rate（VRR）were compared among nodules of different compositions and sizes. The correlation between ablation energy and VRR was analyzed based on nodule volume and composition.Results Over time，the VRR of all three nodule types（solid group 77 cases；cystic group 95 cases；mixed group 19 cases）progressively increased，with significant effects observed for time ，group，and their interaction（Ftime=39.288，Ptime＜0.01；Fgroup=6.177，Pgroup<0.01；Finteraction=4.299，Pinteraction＜0.01）. When stratified by volume［（20-30 mL group（95 cases）； ＞30-40 mL group（45 cases）；＞40 mL group（51 cases）］，significant effects were also found for time，group，and interaction（Ftime= 159.085，Ptime ＜0.01；Fgroup=34.861，Pgroup ＜0.01；Finteraction= 10.323，Pinteraction ＜0.01）. Correlation analysis showed that both total microwave energy and energy per unit volume were negatively correlated with VRR at 24 months（P<0.05）. The main treatment-related complication was pain（90.1%），and 9 patients（4.7%）experienced transient voice changes.Conclusion MWA is a safe and effective treatment for large benign thyroid nodules. Greater cystic content and larger initial nodule volume were associated with better ablation outcomes. Ablation energy was negatively correlated with VRR.